Tool path generation for chamfering drill holes of a pipe with constant width. (September 2016) - Sato, Takato; Sato, Youichi; Maekawa, Takashi
Abstract: When drilling circular holes into metal circular pipes, burr is generated at the hole entrance as well as at the hole exit. The burrs generated at the edge curves associated with the outer and inner pipe surfaces must be removed by constant chamfering. Geometrically, the two edge curves can be defined as cylinder-to-pipe intersection curves. In this paper, we employ differential geometric properties of the surface-to-surface intersection curves in order to generate an interference-free tool path with constant chamfering for a ball-end cutter. We demonstrate the effectiveness of our method by conducting experiments with physical pipe models. Graphical abstract: Highlights: An efficient and accurate automatic collision-free tool path is generated. Burrs are removed with constant chamfering. The cutter contact point passes through the center line of the chamfering surface.